Influence of Deposition Pressure on Component Composition and Properties of Barium Strontium Titanate Thin Films - A. G. Altynnikov; A. G. Gagarin; M. V. Zlygostov; A. Y. Popov; S. V. Razumov; A. V. Tumarkin (Известия высших учебных заведений России: Радиоэлектроника, 2016)
Influence of deposition pressure on the properties of ferroelectric barium strontium titanate thin films obtained by RF magnetron sputtering has been investigated. It has been shown that the deposition pressure affects the component composition of the films as the spatial zone of atomic particle thermalization changes significantly. Influence of deposition pressure on growth rate and, hence, on film thickness has been studied.